Discrete-element modelling of rock breakage using dense random packing agglomerates. Issue 3 (18th September 2013) - Li, H; Lowndes, I; McDowell, G. R.
Abstract : In recent years, agglomerates have been used to investigate the fracture of soil particles and rocks using discrete-element modelling (DEM). Hexagonal closed packing (HCP) and the radius expansion methods are the two most popular algorithms used to produce agglomerates. However, the HCP agglomerates created are highly anisotropic. Agglomerates created by the radius expansion method are too porous and are therefore not dense enough to represent rock. This paper proposes a new method to form dense random packing agglomerates. An agglomerate model that is isotropic and nearly stress-free (there is a small degree of particle overlap) is presented. To achieve agglomerates that mechanically behave like rock, the method produces smaller and smaller particles to fill smaller and smaller voids. The packing density achieved is governed by the ratio of the radius of the largest and smallest spheres. Numerical simulations of diametral crushing tests have been performed on the model agglomerates. Analysis reveals that as the density of the agglomerate increases, the isotropy of the particle improves and the variability of the strength of agglomerates formed from the same size distribution of spheres is reduced.